2021
DOI: 10.1111/1756-185x.14172
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with low back pain in schoolchildren in Cameroon, sub‐Saharan Africa

Abstract: Background Data on the prevalence and factors associated with low back pain (LBP) in schoolchildren are scarce in Africa, particularly in sub‐Saharan Africa. Objectives To assess the prevalence and factors associated with LBP in schoolchildren in Cameroon. Patients and methods We performed a cross‐sectional study in 10 randomly selected schools (public and private) in Douala, Cameroon. Using a self‐administrated questionnaire, sociodemographic, usual physical activity, and clinical data were collected and all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…The author concluded that there a correlation between excessive weight carried in the backpack with the appearance of postural changes and pain among students. In the study by Lekpa et al (2021) 15 who evaluated 1070 schoolchildren in Douala, Cameroon, no correlations were observed between the weight of backpacks and the presence of low back pain. In study, the mean weight of backpacks below 10% of the students' body weight was also found, and the factors associated with low back pain were female sex, practice of competitive sports, sitting position and low back pain in the evaluated family members.…”
Section: Discussionmentioning
confidence: 94%
“…The author concluded that there a correlation between excessive weight carried in the backpack with the appearance of postural changes and pain among students. In the study by Lekpa et al (2021) 15 who evaluated 1070 schoolchildren in Douala, Cameroon, no correlations were observed between the weight of backpacks and the presence of low back pain. In study, the mean weight of backpacks below 10% of the students' body weight was also found, and the factors associated with low back pain were female sex, practice of competitive sports, sitting position and low back pain in the evaluated family members.…”
Section: Discussionmentioning
confidence: 94%
“…Back pain was associated with prolonged sitting (Kemta et al, 2021;Masiero et al, 2021) and incorrect sitting posture (Minghelli, 2020a;Meziat-Filho et al, 2017). Minghelli (2020a) highlights the importance of this aspect, given the high number of hours' students spend sitting in schools.…”
Section: D2) Analysis Of the Records Found On The Prevalence Of Back ...mentioning
confidence: 99%
“…Other risk factors pointed out by the scientific literature are: incorrect adjustments of school furniture (Ayed et al, 2019;Dianat et al, 2017); posture during the handling of electronic devices and the time spent using them (Vitta et al, 2021;Masiero et al, 2021;Bento et al, 2020;Minghelli, 2020a;Ayed et al, 2019); time spent watching television (Santos et al, 2021;Noll et al, 2021;Bento et al, 2020;Ayed et al, 2019;Oka et al, 2019;Paranjape e Ingole, 2018;Meziat-Filho et al, 2017); lack of adequate rest (Masiero et al, 2021;Muñoz-Serrano et al, 2021); high BMI (González-Gálvez et al, 2020;Spiteri et al, 2017); presence of lumbar hyperlordosis (Sainz de Baranda et al, 2020b); family history of back pain (Kemta et al, 2021;Noll et al, 2021;Masiero et al, 2021;Oka et al, 2019;Noormohammadpour et al, 2019;Dianat et al, 2017); passive smoking (Noormohammadpour et al, 2019).…”
Section: D2) Analysis Of the Records Found On The Prevalence Of Back ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The previous African studies published on JOBP were surveys or cross-sectional studies performed in schools without medical imaging to obtain a differential diagnosis ( 9 , 14 17 ). Only one study included clinical examination in its design, but no medical imaging was performed ( 9 ).…”
Section: Introductionmentioning
confidence: 99%